Nonmammalian gonadotropin-releasing hormone molecules in the brain of promoter transgenic rats - Parhar, Ishwar S. (National Academy of Sciences, 2005)
Mammalian gonadotropin-releasing hormone (GnRH1) and nonmammalian immunoreactive GnRH subtypes were examined in transgenic rats carrying an enhanced GFP (EGFP) reporter gene driven by a rat GnRH1 promoter. Double-label immunocytochemistry was performed on EGFP(+)/GnRH1 brain sections by using antisera against GnRH1, GnRH2 (chicken II), GnRH3 (salmon), or seabream GnRH. EGFP(+)/GnRH1 neurons were in the septal–preoptic hypothalamus but not in the midbrain, consistent with GnRH1-immunopositive neurons in WT rats. Apparent coexpression of EGFP(+)/GnRH1 with other GnRH subtypes was observed. All EGFP(+) neurons in the septal–preoptic hypothalamus were GnRH1-immunopositive. However, only ≈80% of GnRH1-immunopositive neurons were EGFP(+), which awaits further elucidation. GnRH subtypes-immunopositive fibers and EGFP(+)/GnRH1 fibers were conspicuous in the organum vasculosum of the lamina terminalis, median eminence, and surrounding the ependymal walls of the third ventricle and the aqueduct in the midbrain. These results demonstrate that the expression of the EGFP–GnRH1 transgene is restricted to the bona fide GnRH1 population and provide clear morphological evidence supporting the existence of GnRH1 neuronal subpopulations in the septal–preoptic hypothalamus, which might be driven by different segments of the GnRH promoter. This genetic construct permits analyses of promoter usage in GnRH neurons, and our histochemical approaches open questions about functional relations among isoforms of this peptide, which regulates reproductive physiology in its behavioral and endocrine aspects.